PELATIHAN EMPATI UNTUK MENURUNKAN PERILAKU BULLYING PADA PELAKU BULLYING SISWA SMP - Putri Franenda Shintya Dewi (Universitas Islam Indonesia, 2023)
ABSTRACT : This study aims to determine the effect of empathy training to reduce bullying behavior. The design used is a one grop pretest and posttest design. Subjects 8 students with an age range of 12 – 14 years who were bullies at school. The measuring instrument uses a scale of bullying and empathy. Data analysis used paired sampel t-test to see differences in bullying behavior and empathy before and before the intervention was given. The result showed tahat there was a decrease in the score of bullying behavior during the intervention posttest with a vale of 19,887 and p-vale = 0.000 (<0.05) while the empathy score during the posttest after the intervention decreased with a value of - 8.922 and p-vale = 0.000 (<0,05). The implication of this research is that empathy training based on an experiential learing approach can be used as a method to reduce bullying behavior.